Supporting Marine Energy Project Developments in the U.S.: A Toolkit for Siting and Permitting (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Marine energy development in the United States presents significant opportunities for international developers but faces numerous challenges related to siting and permitting (consenting). Developers must navigate a complex landscape of federal, state, and local regulations while accounting for spatially variable factors such as protected species and sensitive habitats, designated marine protected areas (MPAs), and diverse community power interests and needs. The dynamic nature of these considerations can complicate project planning and regulatory compliance, potentially hindering the deployment of clean marine energy technologies.To address these challenges and assist the permitting process for Marine Energy (ME) development in the U.S., a comprehensive ME Toolkit has been developed and made publicly available. This one-stop resource integrates spatial databases and regulatory information to provide essential insights for site and regional assessments in the U.S. Key features of the ME Toolkit include:• Regulatory Pathway Guidance and Documentation: Clear, federal and state-specific permitting information to streamline regulatory navigation and ensure compliance at all governance levels, including examples from actual permitting documentation.• Spatial Data Integration: Comprehensive environmental data layers representing protected species, sensitive habitats, and jurisdictions (e.g., MPAs), as well as constraints including marine protected areas.• Site and Regional Exploration: Flexible tools allowing users to evaluate project-specific sites or broader regional areas to identify optimal locations for development.Each of these “layers” of information can inform advanced siting, permitting, and potential mitigation needs. Stepwise, beginning with understanding locations with suitable wave and tidal resources, then layering on locations with constraints such as legislated marine protected areas and sanctuaries, provides a starting point for diving into further potential environmental interactions that may require avoiding, minimizing or mitigating environmental impacts, such as protected species or sensitive habitats. The ME Toolkit's ability to support both site-specific and regional-scale planning positions it as a critical asset for the evolving landscape of marine energy in the U.S. Renewed interest in marine spatial planning, such as California’s recent legislative efforts (Senate Bill 605), underscores the importance of proactive, data-driven approaches to ocean resource management. Similar initiatives may be emerging in other regions, further emphasizing the need for robust tools like the ME Toolkit to facilitate efficient and environmentally responsible marine energy development.By providing ME developers and regulators with actionable insights and streamlining complex regulatory pathways, the ME Toolkit empowers the advancement of marine energy projects in the U.S. that meet both technical and ecological considerations. This presentation will highlight the ME Toolkit's functionalities, explore its real-world applications, and discuss its role in shaping the future of sustainable marine energy deployment across U.S. waters.